Dietary biomarkers of ultra-processed foods: A narrative review - Thomas Scott Armstrong; Kaitlyn Delaney Chappell; Lekan Ajibulu; Karen Wong (Clinical Nutrition Open Science)
Summary: The rapidly increasing prevalence of ultra-processed foods (UPFs) in global diets necessitates a more comprehensive understanding of this food group's effects on health and disease. Nutritional biomarkers are critical for developing this understanding, as they provide an objective assessment of the body's response to UPF intake. Here, we critically assessed the findings of five studies-all of which were identified via a systematic search of the literature using stringent criteria and were focused on the biomarkers of UPFs. Based on the data extracted, we categorized UPF biomarkers into organic acids (including amino acids), lipids/lipid-like molecules, xenobiotic food components (specifically associated with UPFs), and other molecular compounds (dietary oxysterols, nucleotides, proteins, etc). These findings emphasized the importance of future studies concerning UPF and food processing techniques, while providing a succinct summary of the current biomarkers of UPFs in relevant literature.